Mengatasi Keragaman Gaya Belajar pada Pendidikan Tinggi dan Vokasi Melalui Pengembangan E-learning Adaptive Hypermedia System Berbasis Moodle - Toni Setiawan; R. Irlanto Sudomo (Edukasia Islamika : Jurnal Pendidikan Islam, 2019)
The diversity of learning styles arises when input to higher education and especially vocational education comes from various sources, including high school (senior high school) or MA (Madrasah Aliyah) and from vocational (Vocational High School) or MAK (Madrasah Aliyah Vocational), so students have a diverse learning style. This research is type of R&D (Reseach and Development), the research procedure consists of: 1) make the needs analysis of products that will be developed based on the potential and problems of moodle-based adpaptive hypermedia; 2) reviewing the study of literature and information by observation; 3) designing basic products; 4) expert validation; 5) revision of product design; 6) designing media; 7) perform a functional trial; 8) first product revision; 9) user trials; 10) second product revision; 11) product implementation. The results of this reseacrh are adaptive hypermedia with link http://www.evodu.net/. E-learning adaptive hypermedia is designed specifically for college students and vocational education with diverse learning styles